The Impact Of Atv ( All-Terrain Vehicle) Tourism Activities On The Economic Conditions Of The Community In Singapadu Kaler Village - pradnyana, wahyu (Cita konsultindo, 2025)
This study analyzes the impact of ATV (All-Terrain Vehicle) tourism activities on the economic conditions of the community in Singapadu Kaler Village, Gianyar Regency. The research aims to identify the current tourism conditions, tourist characteristics, and the direct, indirect, and long-term economic impacts of ATV tourism activities. The study employs a mixed-method approach, combining qualitative and quantitative descriptive approaches. Data were collected through observation, interviews, and the distribution of questionnaires to tourists, business owners, and workers involved in ATV tourism. The results indicate that ATV tourism has a positive economic impact on the local community through increased income, employment absorption, and the development of small businesses supporting ATV tourism. However, challenges in sustainable management, such as environmental degradation and potential conflicts among business actors, are also present. This study recommends integrated management involving the government, the community, and business actors to support the sustainability of ATV tourism.